HEURISTIC LEARNING IN PRIMARY NATIVE LANGUAGE EDUCATION (Conferencea, 2023)
In this article, the development of tools that reveal the possibilities of using ethnopedagogy, which is widely used in world pedagogy, the research of the methodology of using some methods of teaching in the native language education, the specific characteristics of these methods at the educational stages, and the comparative study based on the analysis attention is paid to issues such as exit.